AN ANALYSIS OF SCIENCE LITERACY SKILL FOR STUDENTS THROUGH GUIDED INQUIRY ON COLLOID SUBJECT AT XI GRADE IN SAMARINDA - Iis Intan Widiyowati (PROSIDING SEMINAR KIMIA, 2015)
The effort in developing science literacy for students can be done through the process of learning science. This process gives changes for students to embrace science completely, instead of teaching science only based on information. Solving the problem of topic discussion will be the design of learning process. Within this process, it needs a model that facilitates students to get a maximum meaningful learning that also involves students’ participation in learning process. Wenning (2007), in his journal Assessing Inquiry Skills as a component of Scientific Literacy,stated that the skill of science literacycan be discovered through measuring students’ inquiry skill. In this topic, inquiry skill means the ability to investigate. The results of the research above show that guided inquiry learning model is able to give positive influence to students’ science literacy.This research used a qualitative descriptive method. The aim of this method was to discover fact, situation, variable and phenomena that encounter while analyzing a research and representing it as the way it was(Notoatmojo, 2012). In this research, the researcher used a descriptive design to delineate the fact or certain population characteristic systematically, factually and accurately in order to know the students skill in science literacy. The data collection technique in this research was a qualitative data gained from written test, interview, and documentation. The average percentage of students' science literacy in three domains (content, context and process) includes in good category. Achievement percentage in the content domain by 71.50%, context domain by 67%and process domain by 84%. It is relevant to Ibrahim & Aspar (2006) that there was a relationship between knowledge and application of science. Thus the high of oneof science literacy domain will affect other science literacy domain. Judging from the aspect of content percentage of 71.50%, which means mastery of the concepts of science (colloidchemistry) is good. Judging from the aspect of student science content,it is obtained achievement by the percentage of 64%. This indicates that colloid chemistry learning has been linked with students' everyday real life.